Pendampingan Masyarakat Desa Parangtritis dalam Pengelolaan Kawasan Gumuk Pasir melalui kegiatan Diversifikasi Usaha Berbasis Sumberdaya Pesisir - Djaka Marwasta (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
Barchan types of sand dune region (barchanoid dunes) is a geographic landmark that is formed by the activity of wind that precipitated to form resembles a crescent moon. In general, sandbanks formed in the desert area, however, but uniquely, it is formed in Indonesia wich is tropical zone and has high rainfall. Therefore, the formation of sand dunes in the Parangtritis village is the only one in Indonesia, and even in Southeast Asia. The purpose of community service program are (1) improve the understanding of the community and the partners on sustainable development through the implementation of Community Services; (2) promote knowledge-based Conservation of sand dunes to local partnerships, cooperation, society, government, and other stakeholders.The methods in the implementation of community service programs include: (1) the initial observation, (2) mapping the problems, (3) dissemination, (4) FGD by involving sand dunes users, (5) assistance program to the public, i.e advocacy on “rembug warga” to determine the programs that will be organized in order to use sand dunes wisely (6) workshop on the conservation of sand dunes and creative economic activity, and (7) the documentation and exploration.Output of this community service programs are: (1) increasing the capacity of institutions and stakeholders; (2) increasing the involvement and range of universities in community service programs; (3) the increased adoption of expediency results of research activities and community service for the wider community; and (4) dissemination of activity results in the form of products publication. Outcome obtained from this activity is a collective commitment to develop Desa Parangtritis in order to realize the vision of